Difference of neointimal growth patterns in bifurcation lesions among four kinds of drug‐eluting stents. Issue 5 (14th February 2014) - Yoshimura, Takahiro; Tanaka, Akihiro; Mori, Naoki; Nakamura, Daisuke; Taniike, Masayuki; Makino, Nobuhiko; Egami, Yasuyuki; Shutta, Ryu; Tanouchi, Jun; Nishino, Masami
<x xml:space="preserve">Abstract</x> Aim: Neointimal proliferation of bifurcation lesions after implantation of drug‐eluting stents (DES) has not been well evaluated. Thus, we compared neointimal proliferation of bifurcation lesions among four DES using optical coherence tomography (OCT). Methods: 8‐month follow‐up OCT was performed in 68 bifurcation lesions treated by 15 sirolimus‐eluting stents (SES) and 17 paclitaxel‐eluting stents (PES) as first‐generation DES, and by 17 zotarolimus‐eluting stents (ZES) and 19 everolimus‐eluting stents (EES) as second‐generation DES. Cross‐sectional images of the bifurcation lesion using OCT were analyzed every 450 µm. All images were divided into three areas: inner wall of the bifurcation (IB), outer wall of the bifurcation (OB), and ostium of the side branch (SB). We compared the incidence of uncovered struts (IUS) among three areas and the averaged neointimal thickness (NIH) between IB and OB in each stent and also compared these OCT parameters among all DES. Results: There were no significant differences of IUS between IB and OB in second‐generation DES, while in first‐generation DES, IUS of IB and OB showed significant differences. The IUS of SES in both areas was significantly higher than in the other DES (all P < 0.001). PES had a significantly higher IUS in SB than the others (all P < 0.001). NIH of OB was significantly higher than that of IB in PES, ZES, and EES, but in SES the NIH was similar in the two areas. Conclusions: OCT revealed different neointimal growth patterns among SES, PES, ZES, and EES in bifurcation lesions. © 2014 Wiley Periodicals, Inc.